Knowledge of Students at the State Islamic University Syekh Ali Hasan Ahmad Addary Padangsidimpuan Regarding Religious Moderation - Pahri Siregar; Juntika Nurihsan; Syamsu Yusuf LN; Nandang Budiman; Ridwan Gofur (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2022)
This study examines religious Moderation among the State Islamic University Syekh Ali Hasan Ahmad Addary Padangsidimpuan students, characterized by ethnic and religious diversity. A mixed-method approach was used, including a quantitative survey with the Rasch Model and qualitative interviews. The study population consists of 433 students from the 2021 and 2022 cohorts across four faculties: Tarbiyah and Teaching Sciences (55.4%), Da'wah and Communication Sciences (22.4%), Islamic Economics and Business (16.2%), and Sharia and Law Sciences (6.0%). Findings reveal that most students fall into the very moderate (58.85%) and moderate (40.36%) categories, with a significant gender difference, where females are generally more moderate than males. The categories of religious Moderation are divided into very moderate, moderate, and less moderate based on value intervals and ideal scores, indicating that religious Moderation among students is generally balanced and tolerant. The analysis provides a comprehensive view of moderation tendencies, underscoring the importance of religious Moderation in fostering a peaceful and harmonious society